From Africa to Asia: The Parenting Odyssey of African Mothers in China - Ujuagu, Gloria Ifeoma; Yu, He; Alabi, Victoria; Ying, Haihua; Gu, Jintu (Technium Social Sciences Journal, 2025)
The movement of humans from one country to another in search of greener pastures over the years has become more pronounced. In the ever-evolving landscape of global migration, of particular interest is the migration of African mothers to China. Hence, the experiences of African mothers raising their children in China stand as a compelling narrative, ripe for exploration. By employing a well-structured interview, this qualitative study explored the multifaceted realities faced by this unique demography. Participants in the study were African mothers from five different African countries, namely, Nigeria, Ghana, Kenya, Burundi, and Zimbabwe, living in China. Traversing the intersections of race, gender, and migration, the study illuminates the nuanced strategies employed by African migrant mothers as they negotiate their identities and parenting approaches. From the daunting language barriers to the navigation of shifting societal norms, these resilient women navigate a complex web of obstacles, all while striving to provide their children with a sense of belonging and a strong cultural foundation. By unveiling the unique challenges and coping mechanisms of African migrant mothers in China, this study further brings to the limelight the intricate interplay between cultural identity, parenting practices, and the challenges of adapting to a foreign environment. Understanding the resilience, adaptation, extraordinary lives, and universal bonds of African migrant mothers in China, this study offers a window into the complexities of the migrant experience and the remarkable strength that transcends borders.